Oxygen Therapy Delivery and Body Position Effects Measured With Electrical Impedance Tomography - Yuan, Zhiyong; Han, Xiaoning; Wang, Lisha; Xue, Ping; Sun, Yunbo; Frerichs, Inéz; Möller, Knut; Xing, Jinyan; Zhao, Zhanqi (Respiratory care, 2020)
The aim of this prospective randomized crossover study was to compare the short-term effects of high-flow nasal cannula (HFNC) therapy and a 45° head-up tilt to the short-term effects of conventional oxygen (O ) therapy in post-abdominal surgery patients. A total of 18 subjects who were successfully weaned from ventilator support after abdominal surgery were included in the study. The subjects were randomly assigned to 2 groups: conventional O was applied in group A for 15 min, and HFNC (60 L/min) was applied in group B for 15 min. A 15-min washout period with conventional O was performed before the interventions were switched in both groups. Heart rate, blood pressure, breathing frequency, ratio of arterial partial pressure of oxygen to the fraction of inspired oxygen (P /F ), and subject-reported comfort scores were recorded. Changes in end-expiratory lung impedance (EELI) were calculated with electrical impedance tomography. Results are presented as the percent change in lung volume compared to baseline during volume-controlled continuous mandatory ventilation before extubation. HFNC improved EELI in both the ventral (conventional O vs HFNC, -48.2% ± 41.0 vs -30.0% ± 40.3, < .001) and the dorsal (conventional O vs HFNC, -37.0% ± 75.9 vs -26.5% ± 68.4, = .02) regions of the lungs. Subjective subject-reported scores indicated that HFNC was more comfortable than conventional O (conventional O vs HFNC, 5.8 ± 1.5 vs 6.9 ± 1.9, = .02). No differences were found in the other examined parameters. A head-up tilt position with conventional O improved EELI in the dorsal regions (55.9% ± 100.1, < .001) but not in the ventral regions (-37.9% ± 43.1%, = .38) of the lungs compared to HFNC or conventional O alone. In post-abdominal surgery subjects who had been extubated, HFNC improved lung volume and patient comfort. A head-up tilt position introduced a heterogeneous increase in EELI in the dorsal regions of the lungs. HFNC therapy may be beneficial in this patient group. (ChiCTR1900020886, http://chictr.org.cn).